Bifunctional Electrocatalysts for Overall and Hybrid Water Splitting - Quan, Li; Jiang, Hui; Mei, Guoliang; Sun, Yujie; You, Bo (Chemical reviews, 2024)
Electrocatalytic water splitting driven by renewable electricity has been recognized as a promising approach for green hydrogen production. Different from conventional strategies in developing electrocatalysts for the two half-reactions of water splitting (e.g., the hydrogen and oxygen evolution reactions, HER and OER) separately, there has been a growing interest in designing and developing bifunctional electrocatalysts, which are able to catalyze both the HER and OER. In addition, considering the high overpotentials required for OER while limited value of the produced oxygen, there is another rapidly growing interest in exploring alternative oxidation reactions to replace OER for hybrid water splitting toward energy-efficient hydrogen generation. This Review begins with an introduction on the fundamental aspects of water splitting, followed by a thorough discussion on various physicochemical characterization techniques that are frequently employed in probing the active sites, with an emphasis on the reconstruction of bifunctional electrocatalysts during redox electrolysis. The design, synthesis, and performance of diverse bifunctional electrocatalysts based on noble metals, nonprecious metals, and metal-free nanocarbons, for overall water splitting in acidic and alkaline electrolytes, are thoroughly summarized and compared. Next, their application toward hybrid water splitting is also presented, wherein the alternative anodic reactions include sacrificing agents oxidation, pollutants oxidative degradation, and organics oxidative upgrading. Finally, a concise statement on the current challenges and future opportunities of bifunctional electrocatalysts for both overall and hybrid water splitting is presented in the hope of guiding future endeavors in the quest for energy-efficient and sustainable green hydrogen production.